2011 IEEE International Conference on Smart Grid Communications (SmartGridComm) 2011
DOI: 10.1109/smartgridcomm.2011.6102333
|View full text |Cite
|
Sign up to set email alerts
|

An approximate dynamic programming approach for coordinated charging control at vehicle-to-grid aggregator

Abstract: Abstract-A vehicle-to-grid (V2G) aggregator is an agent between the power grid and plug-in hybrid electrical vehicles (PHEVs). This paper studies the coordinated charging control of a V2G aggregator, which aims at minimizing the charging cost and reducing the power losses incurred by the fluctuating load. On one hand, a lower cost of charging gives the owners of PHEVs an incentive to cooperate. On the other hand, with an increasing popularity of PHEVs, the impact on the power grid such as power losses should b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…An un coordinated charging infrastructure will create sudden demand upsurges, put constraints on the underlying power grid and at the worst case may lead to failures and outages [9]. The demand of electrical power will be different at different charging station according to number of xEVs deployed or routed per station.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…An un coordinated charging infrastructure will create sudden demand upsurges, put constraints on the underlying power grid and at the worst case may lead to failures and outages [9]. The demand of electrical power will be different at different charging station according to number of xEVs deployed or routed per station.…”
Section: Introductionmentioning
confidence: 99%
“…In the same paper they also proposed a scalable local scheduling optimization problem which can achieve the performance close to that of global counterpart. A real-time approach to TCC is introduced in [9] and similarly real time PCC is addressed in [10] to minimize the power attenuation and shaping voltage profile during PHEV charging process. Request from vehicle or users are processed in [19] and [20] to devise hierarchical aggregator-based hybrid vehicles charging control mechanisms that may lower the variability of demand and distributed power generation through smart charging and discharging in real time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They showed that pricing information is very useful for regulating user demand and balancing the network load. Further research work reported in [10][11][12][13] also investigated the potential use of EV aggregators in different electricity markets.…”
Section: Introductionmentioning
confidence: 99%